2001
DOI: 10.4049/jimmunol.166.12.7477
|View full text |Cite
|
Sign up to set email alerts
|

Mannosylated Lipoarabinomannans Inhibit IL-12 Production by Human Dendritic Cells: Evidence for a Negative Signal Delivered Through the Mannose Receptor

Abstract: IL-12 is a key cytokine in directing the development of type 1 Th cells, which are critical to eradicate intracellular pathogens such as Mycobacterium tuberculosis. Here, we report that mannose-capped lipoarabinomannans (ManLAMs) from Mycobacterium bovis bacillus Calmette-Guérin and Mycobacterium tuberculosis inhibited, in a dose-dependant manner, the LPS-induced IL-12 production by human dendritic cells. The inhibitory activity was abolished by the loss of the mannose caps or the GPI acyl residues. Mannan, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
336
1
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 370 publications
(354 citation statements)
references
References 52 publications
16
336
1
1
Order By: Relevance
“…Based on previous findings described for the treatment of dendritic cells with whole ManLAM, we were interested in determining whether a similar response could be found after the addition of MR blocking antibodies to trimannose-capped bead-treated cells. 23 We found that the addition of MR blocking antibodies recovered IL-12p40 production to a level similar to that observed after TLR2 blocking antibody production (Figure 3), indicating that this may be a response that requires a balance of signaling through both C-type lectin receptors. Based on this diverse range of in vitro macrophage responses to pathogen-derived oligosaccharidecoated beads, we were interested in determining whether these responses would recapitulate when used during in vivo exposure to antigen-presenting cells.…”
Section: Cap Sugars Derived From Manlam Are Required Tlr2 To Elicit Isupporting
confidence: 73%
See 3 more Smart Citations
“…Based on previous findings described for the treatment of dendritic cells with whole ManLAM, we were interested in determining whether a similar response could be found after the addition of MR blocking antibodies to trimannose-capped bead-treated cells. 23 We found that the addition of MR blocking antibodies recovered IL-12p40 production to a level similar to that observed after TLR2 blocking antibody production (Figure 3), indicating that this may be a response that requires a balance of signaling through both C-type lectin receptors. Based on this diverse range of in vitro macrophage responses to pathogen-derived oligosaccharidecoated beads, we were interested in determining whether these responses would recapitulate when used during in vivo exposure to antigen-presenting cells.…”
Section: Cap Sugars Derived From Manlam Are Required Tlr2 To Elicit Isupporting
confidence: 73%
“…11 Loss of this oligosaccharide cap from M. bovis bacillus Calmette-Guerin and M. tuberculosis ManLAM was shown to reverse inhibition of LPS-induced IL-12 production by human dendritic cells. 23 We demonstrated the chemical composition and surface availability of these latex bead-bound cap sugars. 19 Given previous results regarding the effect of the larger pathogen glycoconjugates ManLAM and LPG on critical cytokine production by macrophages and dendritic cells, we used novel bead-linked oligosaccharides to determine the role of these five pathogen-derived cap sugars alone in altering in vitro macrophage cytokine production.…”
Section: Cap Sugars Are Biologically Available On Coated Latex Beadsmentioning
confidence: 92%
See 2 more Smart Citations
“…It is known that DC interact with yeasts essentially by the mannose-binding receptors CD206 [22,31] 32,[34][35][36][37] and TLR2 [32,38,39]. Therefore, we analyzed Candida uptake in the presence of mannan, which binds both CD206 and DC-SIGN [40,41] and interferes with particle internalization by these receptors [42], or laminarin, a specific dectin-1 inhibitor [27,35,40,41,43]. Fig.…”
Section: Receptors Involved In C Albicans Uptakementioning
confidence: 99%